Childhood Renal Tumor: A Report from a Chinese Children's Cancer Group. (24th July 2014) - Cai, Jiaoyang; Pan, Ci; Lu, Qin; Yan, Jie; Ju, Xiuli; Ma, Futian; Zhu, Yiping; Liu, Qiuling; Sun, Lirong; Jiang, Lian; Cao, Lizhi; Li, Fu; et al.
Abstract : Here we investigated the establishment of multicenter cooperative treatment groups in China, as well as radiotherapy compliance and effectiveness among children with renal tumors. Medical records were reviewed for 316 children with renal tumors diagnosed by a multicenter cooperative group from 14 hospitals in China from 1998 to 2012. Median patient age was 29.5 months (range, 2–173 months old), and male-to-female ratio was 1.4 : 1. After a median follow-up of 22 months (range, 1–177 months), five-year event-free survival rates were 72% overall; 76.1% for favorable histology (251 cases); 59% for unfavorable histology (27 cases); and 91%, 75%, 71%, 53%, and 48.5%, respectively for Stages I, II, III, IV, and V. Following standardized criteria, radiation therapy was indicated for 153 patients, among whom five-year event-free survival was 72.8% for the 95 who received radiation and 24% for the 58 patients who did not. Our results are reasonable but can be further improved and show the feasibility of a multicenter cooperative group model for childhood renal tumor treatment in China. Radiation therapy is important for stage III and IV patients but remains difficult to implement in some parts of China. Government management departments and medical professionals must pay attention to this situation. This clinical trial is registered with ChiCTR-PRCH-14004372.